Vancomycin-Induced Thrombocytopenia as a Less Considered Contributing Cause in Differential Diagnosis of Thrombocytopenia: A Case Report - Sholeh Ebrahimpour; Shayda Najafi; Zahra Jahangard-Rafsanjani (Research Center for Rational Use of Drugs (RCRUD), 2019)
Thrombocytopenia has been reported as an adverse effect of numerous medicines including vancomycin. Due to contribution of other suspected causes and lack of a standard diagnostic test, vancomycin-induced thrombocytopenia has been less addressed in clinical practice. In the current study, we present a suspected case initially diagnosed as heparin-induced thrombocytopenia but further workup proposed vancomycin as the offending medicine. Following discontinuation of vancomycin, the thrombocytopenia resolved which confirmed the diagnosis of vancomycin induced thrombocytopenia. We tended to highlight vancomycin-induced thrombocytopenia which is usually not considered in differential diagnosis of thrombocytopenia in comparison with heparin induced thrombocytopenia which is well known for clinicians; a scenario commonly encountered in clinical practice. This is important regard to high possibility of concomitant use of vancomycin and heparin in every day clinical practice. In accordance with educational aims of the current case, differential diagnosis of thrombocytopenia and clinical approach to thrombocytopenia is well documented in this patient.